Coisa de preto e norma de branco: a circulação dos discursos do racismo estrutural nas Instituições do Sistema de Justiça do Maranhão (Polícia Judiciária, Ministério Público e Poder Judiciário) - SILVA JUNIOR, Francisco Carlos da (2019)
The dissertation addresses the circulation of racism discourses of structural racism, notably the discourse of denial of racism, within the scope of the Justice Institutions of the State of Maranhão (Judicial Police, Public Ministry and Judiciary). It problematizes the very rare presence of the word racism in the jurisprudence of the Court of Justice of Maranhão, which in a period of ten years (2008 to 2018) only issued a ruling, which mentions this word. It also discusses the racist genesis of the Brazilian legal system, the uniqueness of racism in Brazil and Maranhão, highlighting the manifestation of bravery as one of the devices for producing the discourses of structural racism. Based on a theoretical framework that establishes a dialog between Marxist social theories and Foucaultian studies, this work adopted as methodological procedure. The material that is part of the corpus of the investigation is the case of the three cases that were processed in the institutions of the Justice System, processes related to denunciations of racist practices, and which presented as a point of convergence the incidence of the discourse of denial of racism. The manifestation of the prohibition of racism in the order of discourses, related to structural racism, that circulated in the institutions of the Maranhense justice system.